Novel PTRF mutation in a child with mild myopathy and very mild congenital lipodystrophy - Ardissone, Anna (BioMed Central, 2013)
BACKGROUND: Mutations in the PTRF gene, coding for cavin-1, cause congenital generalized lipodystrophy type 4 (CGL4) associated with myopathy. In CGL4, symptoms are variable comprising, in addition to myopathy, smooth and skeletal muscle hypertrophy, cardiac arrhythmias, and skeletal abnormalities. Secondary features are atlantoaxial instability, acanthosis nigricans, hepatomegaly, umbilical prominence and metabolic abnormalities related to insulin resistance, such as diabetes mellitus, hyperlipidemia and hepatic steatosis. CASE PRESENTATION: We describe a 3 year-old child of Moroccan origin with mild muscle phenotype, mainly characterized by mounding, muscle pain, hyperCKemia and mild caveolin 3 reduction on muscle biopsy. No CAV3 gene mutation was detected; instead we found a novel mutation, a homozygous single base pair deletion, in the PTRF gene. Only after detection of this mutation a mild generalized loss of subcutaneous fat, at first underestimated, was noticed and the diagnosis of lipodystrophy inferred. CONCLUSIONS: The PTRF gene should be investigated in patients with hyperCKemia, mild myopathy associated with spontaneous or percussion-induced muscle contractions like rippling or mounding, and no CAV3 mutation. The analysis should be performed even if cardiac or metabolic alterations are absent, particularly in young patients in whom lipodystrophy may be difficult to ascertain.